A season of love - Clipston, Amy. (Grand Rapids, Mich. : Zondervan, 2012)
Three young friends enter the most important season of their lives. But relationships have changed, and only time will tell if Lindsay, Katie, and Lizzie Anne have made the right choices.
Includes discussion quesitons.
Keywords: Amish -- Fiction; Amish Country (Pa.) -- Fiction; Domestic fiction; Christian fiction